ENHANCING GRADE VIII STUDENTS’ VOCABULARY MASTERY THROUGH PICTURES: A QUASI-EXPERIMENTAL STUDY - Mimiyanti Mimiyanti; Mawardin M. Said; Desrin Lebagi; Nur Sehang Thamrin (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aimed to investigate the effectiveness of using pictures in developing the vocabulary mastery of Grade VIII students at SMP Negeri 1 Taopa Parigi Moutong. A quasi-experimental design was employed, involving two classes: an experimental group taught using pictures as instructional media and a control group taught through conventional methods without pictures. The population consisted of 113 Grade VIII students across four classes, and two classes were selected as the sample through random sampling. Data were collected through pre-tests and post-tests consisting of multiple-choice, picture-matching, and fill-in-the-blank items. The vocabulary items tested were limited to nouns, verbs, and adjectives based on the Grade VIII Kurikulum Merdeka syllabus. Data were analyzed using descriptive statistics, normality tests (Shapiro-Wilk), homogeneity tests (Levene's Test), and an Independent Sample T-Test using SPSS version 25. The results showed that the experimental group’s mean score increased significantly from 54.71 in the pre-test to 78.17 in the post-test, while the control group showed only a slight increase from 53.29 to 55.69. The Independent Sample T-Test yielded a significance value of 0.014 (p < 0.05), indicating a statistically significant difference between the two groups. These findings confirm that the use of pictures effectively enhances students’ vocabulary mastery by providing visual associations that support comprehension and retention. Teachers are therefore encouraged to integrate picture-based media into vocabulary instruction as a practical and engaging alternative to conventional teaching methods.